Malignancy and mortality rates in patients with severe psoriatic arthritis requiring tumour-necrosis factor alpha inhibition: results from the British Society for Rheumatology Biologics Register. (21st August 2018) - Fagerli, Karen M; Kearsley-Fleet, Lianne; Mercer, Louise K; Watson, Kath; Packham, Jon; Symmons, Deborah P M; Hyrich, Kimme L
Abstract: Objective: The aim of this study was to compare the incidence of cancer and all-cause and cause-specific mortality rates among a cohort of patients with severe PsA receiving TNF inhibitor (TNFi) with those of the general UK population. Methods: Cancers and deaths were identified from the national cancer and the national death registers in patients with PsA included in the British Society for Rheumatology Biologics Register from start of TNFi until 31 December 2012. Standardized incidence ratios (SIRs) and standardized mortality ratios (SMRs) were calculated using published cancer and death rates for the general population. SIRs were calculated for both overall cancer risk and non-melanoma skin cancer. SMRs were calculated for (1) all-cause mortality, (2) death from malignancy and (3) death from circulatory disease. Gender-specific analyses were also performed. Results: Thirty-four cancers and 41 deaths among 709 patients were observed. The risk of malignancy overall was not increased (SIR 0.94; 95% CI: 0.65, 1.34). However, there was a significantly increased incidence of non-melanoma skin cancer (SIR 2.12; 95% CI: 1.19, 3.50). The all-cause mortality rate in our cohort was increased (SMR 1.56; CI: 1.12, 2.11). Death from malignancy was not increased, but death from coronary heart disease was increased (SMR 2.42; 95% CI: 1.11, 4.59). Conclusion: In our cohort of patients with severe PsA, the overall incidence of malignancy was similar to that of the general population, although the incidence of non-melanoma skin cancer was increased. All-cause mortality was significantly increased, in part due to excess of deaths attributed to coronary heart disease.